Kesetaraan Gender Dalam Al-Quran - Fauziah, Syarifah (PSW, 2012)
Abstract: This article discusses gender equality in the view of the Qurâan. The raised issues include what gender is and how gender in view of the Qurâan is. One of the central themes ass well as the fundamental principles of islam is an egalitarian principle of equality among human beings that both men and woman are the same among nations, tribes, and ancestry. Al-Qurâan gives us the assertion of equality between men and women and also erode completely the view that there is a difference between both of them. Any differences due to the quality value of devotion to god almighty.Gender is a concept that is used to identify the differences between men and women in terms of socio-cultural influences. Gender in this sense is a form of engineering societies, rather than something that is natural.Gender equality in the Qurâan include: men and woman a like as a servant, both became caliph on earth, equally bound primordial covenant, were both involved in thecosmic drama and in matters of professional career.